National update on measles cases and outbreaks — United States, January 1 – October 1, 2019. Issue 1 (2nd January 2020) - Patel, Manisha; Lee, Adria D.; Clemmons, Nakia S.; Redd, Susan B.; Poser, Sarah; Blog, Debra; Zucker, Jane R.; Leung, Jessica; Link‐Gelles, Ruth; Pham, Huong; Arciuolo, Robert J.; Rausch‐Phung, Elizabeth; et al.
Abstract : This report summarizes the cases of measles reported since January 2019 and identifies the types of communities at high risk for outbreaks of vaccine‐preventable diseases.